WHEN AI BECOMES HUMAN: LOVE AND BELONGING NEEDS IN I AM MOTHER (2019) FILM - Supardi, Moh; Khoirunnisa, Fahira (Universitas Islam Negeri Sunan Gunung Djati, 2024)
The paper aims to examine the cast of artificial intelligence (AI) character in solving the problem of love and belonging needs in I am Mother film. Today, the arise of artificial intelligence (AI) has brought controversial debate among society about ethical consideration and psychological problems. One of the concerns is that the integration of AI with character may open up new approaches and innovation toward AI. The data are qualitatively-described focusing on psychological problems of main character using the third level of the hierarchy of human needs of Abraham Harold Maslow. The data are collected from dialogue, visual capture, and cinematography of I am Mother film. The study reveals that AI has a significant influence on the main character's sense of loss of love and belonging. In this film, the main character undergoes loss of love and belonging needs in four forms, family relationships, friendships, romantic relationships, community, and social group. Consequently, the loss of love and belonging has affected the main character’s psychology, feelings of loneliness, isolation, and emotional instability. Fortunately, the main character (Daughter) can overcome her psychological problems, such as creating a close relationship with Mother, improving her self-development, having empathy and caring for their environment, searching for the truth in the outside world, and finding the truth and where she belongs. The study concluded that AI’s emotion still needs to be controlled and trained to make up something, such as how to express emotion and feeling because the AI doesn’t understand the context since they are still need human involvement in its process of development.